MINAT MEMBACA DAN PEMAHAMAN SISWA KELAS 1 SD MELALUI MEMBACA NYARING, BERCERITA DAN MENULIS KATA YANG DIAWALI HURUF "M" DENGAN PEMANFAATAN BUKU NON TEKS PEMBELAJARAN BAHASA INDONESIA - Basori, Indrianto Setyo; Devi Yulianti (JOURNAL SAINS STUDENT RESEARCH, 2025)
This study aims to foster reading interest, vocabulary comprehension, and story comprehension in early grade students through reading aloud and developmentally appropriate learning. This study employed a descriptive qualitative approach. Data collection techniques included observation, interviews, and documentation. The results of this study indicate that teachers' implementation of reading aloud in Indonesian language learning can improve students' comprehension of the stories they read. Spelling and spelling words beginning with the letter "m" helps with vocabulary comprehension and improves basic writing skills. This learning activity is part of the Indonesian language subject because it can contribute to the achievement of basic literacy skills in first-grade elementary school students.